“I've been having these weird thoughts lately...”: Conspiratorial hermeneutics and metareflexive depictions of fan practices in the Kingdom Hearts franchise - Bowman, Dean (Loading)

(untitled) (Canadian Game Studies Association, 2022)
This paper draws on the theory of mastermind narration developed by M.J. Clarke in the context of prestige television dramas with highly complex non-linear narratives and inconsistent characters (Clarke, 2012) and Jason Mittell’s (2015) concept of ‘forensic fandom’ to offer a reading of the Kingdom Hearts (Square Enix, 2002-) franchise in light of postmodern practices of textual consumption characteristic of current fandoms, such as those explored by Henry Jenkins (2006) and Matt Hills (2002), but also addressing Japanese theorists Hiroki Azuma (2009) and Eiji Ōtsuka’s (2010) work around the notion of the Otaku. I argue that the series’ significant deviation from Disney’s traditional approach to narrative (Wasko, 2001) indicates a desire for the corporation to explore radical new forms of textual production, and to negotiate emerging fan consumption practices within the safe environment of a controlled and licensed text. Just as cultural theorists like Clarke and Anne Allison (2006) argue that a textual product can often contain traces that reflect its wider conditions of production, I propose that the Kingdom Hearts franchise can be read allegorically as an extended experiment by Disney into new forms of collaborative storytelling. I attempt to demonstrate this by concluding with an exploration of the metareflexive depiction of the fan practice of cosplay.